Specificity in plant-mycorrhizal fungal relationships: prevalence, parameterization, and prospects - d’Entremont, Tyler W.; Kivlin, Stephanie N. (Frontiers in Plant Science, 2023)
Species interactions exhibit varying degrees of specialization, ranging from generalist to specialist interactions. For many interactions (e.g., plant-microbiome) we lack standardized metrics of specialization, hindering our ability to apply comparative frameworks of specificity across niche axes and organismal groups. Here, we discuss the concept of plant host specificity of arbuscular mycorrhizal (AM) fungi and ectomycorrhizal (EM) fungi, including the predominant theories for their interactions: Passenger, Driver, and Habitat Hypotheses. We focus on five major areas of interest in advancing the field of plant-mycorrhizal fungal host specificity: phylogenetic specificity, host physiology specificity, functional specificity, habitat specificity, and mycorrhizal fungal-mediated plant rarity. Considering the need to elucidate foundational concepts of specificity in this globally important symbiosis, we propose standardized metrics and comparative studies to enhance our understanding. We also emphasize the importance of analyzing global mycorrhizal data holistically to draw meaningful conclusions and suggest a shift toward single-species analyses to unravel the complexities underlying these associations.